2019
DOI: 10.3389/fimmu.2019.01511
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates LPS-Induced Acute Depressive-Like Behaviors and Microglial NLRP3 Inflammasome Activation Through the SIRT1/Nrf2 Pathway

Abstract: Inflammation is a crucial component of various stress-induced responses that contributes to the pathogenesis of major depressive disorder (MDD). Depressive-like behavior (DLB) is characterized by decreased mobility and depressive behavior that occurs in systemic infection induced by Lipopolysaccharide (LPS) in experimental animals and is considered as a model of exacerbation of MDD. We assessed the effects of melatonin on behavioral changes and inflammatory cytokine expression in hippocampus of mice in LPS-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
206
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(223 citation statements)
references
References 74 publications
(107 reference statements)
17
206
0
Order By: Relevance
“…Melatonin's ability to suppress NLRP3 inflammasome activation and decrease IL-1β hypersecretion, due to its various antioxidant actions, has been fully documented in an LPS/ATP-induced murine microglia model. 33 In the present study, the addition of melatonin was shown to significantly attenuate ROS generation induced by high-dose AFB1. Notably, treatment with melatonin efficiently downregulated the degree of cardiac injury and serum LDH levels in high-dose AFB1-exposed rats.…”
Section: Discussionmentioning
confidence: 49%
“…Melatonin's ability to suppress NLRP3 inflammasome activation and decrease IL-1β hypersecretion, due to its various antioxidant actions, has been fully documented in an LPS/ATP-induced murine microglia model. 33 In the present study, the addition of melatonin was shown to significantly attenuate ROS generation induced by high-dose AFB1. Notably, treatment with melatonin efficiently downregulated the degree of cardiac injury and serum LDH levels in high-dose AFB1-exposed rats.…”
Section: Discussionmentioning
confidence: 49%
“…Compared with wild-type mice, NLRP3 gene knockout mice didn’t exhibit depression-like behaviors in SPT or TST after 4 weeks of CUMS exposure; meanwhile, NLRP3 gene knockout prevented the promotion of IL-1β in serum and hippocampi of CUMS mice ( Su et al, 2017 ). Melatonin, a hormone produced from L-tryptophan mainly in the pineal gland, significantly reversed the depression-like behaviors induced by LPS, which was tightly linked with NLRP3 inflammasome inhibition generated decrease in GSDMD cleavage and pyroptotic cell death ( Arioz et al, 2019 ). In this study, Cy effectively decreased the expression of NLRP3 inflammasome complex and cleaved IL-1β, IL-18, and GSDMD in mice received CUMS modeling, suggesting that Cy-related improvements in depressive behaviors and neuroplasticity defects were partially resulted from the suppression of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…On the model of bacterial pneumonia, LPS-induced ALI mouse model, it was shown that melatonin successfully inhibits pneumonia through interfering with NLRP3 inflammasome, protecting macrophages from pyroptosis [40]. Other publications also demonstrate that melatonin may be an effective inhibitor of pyroptosis and pathologies associated with it [41][42][43][44][45][46].…”
Section: Coronavirus Activates Inflammasome and Causes Inflammation mentioning
confidence: 99%